Adherencia en pacientes con tratamiento de ortodoncia mediante la aplicacion de un instrumento de medicion (2021)
The measurement of adherence to orthodontic treatments is essential, however, many of the measuring instruments do not fulfill the purpose of their application. It is pertinent to bear in mind that adherence is channeled towards two purposes: The effectiveness of the application of the measuring instrument and the continuity to reduce the treatment time. One of the instruments for measuring adherence are databases, there are recorded the times of attendance at appointments, prescriptions given by the specialist. The IUMACO instrument, the reason for this research, may be the most effective when evaluating the results. Electronic methods have recently been introduced that allow knowing when and at what time the patient acquires the medication. The measurement of adherence is not easy and it is necessary to use several methods at the same time to avoid overestimating the results